G64 A survey of transition experiences between paediatrics and adult services for Home Parenteral Nutrition (HPN); A joint BSPGHAN, BIFA and BAPEN project. (7th April 2014) - Kyrana, E; Beath, S; Small, M; Gabe, S; Macdonald, S; Hill, S
Abstract : Aims: The aim was to obtain an overview of current HPN activity and an estimate of future demand for transition services. The survey was aimed at the centres and their experiences, not individual patients. Methods: A questionnaire was dispatched via e-mail in April 2013 to 170 BIFA members with an interest in intestinal failure (IF), and to all 40 BSPGHAN members of the Nutrition and IF working group. Results: 30 replies were received from centres (12 adult, 18 paediatric). The main underlying cause for IF was reported as follows: short bowel syndrome (n 378), small bowel enteropathy (n 96), disorder of motility (n 84), other (n 54). The age distribution was skewed to under 10 yrs and over 30 yrs. The centres were asked to report on the size of the centre and the age range of patients cared for, rather than precise figures (i.e. 0–4, 5–9, 10–20, 21–50, >50 pts). 20/30 respondents reported on transition practices which were: Key worker identified 9(45%); designated clinic 7(35%); Pre-clinic contact by transition worker 11 (55%); post-clinic contact by transition worker 5 (25%); young person own hand held record 2 (10%). 17/30 reported on complications during transition. We estimate about 50% paediatric IF centres, and the largest adult IF centres responded to the survey. The number of teenagers approaching transition is currently around 52. The practices and processes of transition reported were highly variable. One third of respondents identified confusion around care routines and psychological problems at the time of transition. Conclusion: Better service standards relating to timing of initial stages of transition and employment of key worker should be developed. Consideration should be given to check lists for practical aspects (e.g. pumps) as well as psychology input to enhance emotional resilience of the young people and support for carers.